Flame Retardant Synergism of Bentonite and Magnesium Hydroxide in Polypropylene - Yang, Jingwei; Zhang, Jun; Tang, Linsheng (Asian Journal of Chemistry, 2013)
The flammability characterization and synergistic effect of bentonite with magnesium hydroxide in polypropylene have been studied in this work. A synergistic effect on flame retardancy was found when bentonite was incorporated into magnesium hydroxide/polypropylene composites. The mass ratio of magnesium hydroxide and bentonite should be 37:3 and the loading of magnesium hydroxide and bentonite should be 45-50 % to get better flame-retardant effect and mechanical properties according to the experimental results. The flame retardant synergism of bentonite and magnesium hydroxide in polypropylene is further illustrated by the horizontal burning rates. Thermogravimetric analysis revealed that the addition of magnesium hydroxide or bentonite/magnesium hydroxide improves the thermal stability of the composites. The fire performance of polypropylene and polypropylene composites was compared by cone calorimeter test, which indicated that the addition of bentonite/magnesium hydroxide in polypropylene system greatly reduced the heat release rate and mass loss rate.